Attitudes of health professionals working in a university hospital towards ageism - Belgin Oral; Osman Gunay; Fevziye Cetinkaya (Medicine Science, 2019)
This study was carried out to determine the attitudes of health professionals working in Erciyes University Hospitals towards ageism and the related factors. In this cross-sectional study, 351 people working in Erciyes University hospitals and accepting to participate in the research were included. In the statistical analysis, unpaired t-test, one-way ANOVA test (post hoc Scheffe), covariance analysis and Pearson correlation analysis were used. Of the study group 34.8% is male, 65.2% is female and the mean age is 33.6±7.8 years. In the study group, the mean total score of the AAS was 84.5±8.2 and mean score was found to be higher in physicians than nurses and other health professionals. The effect of gender, marital status, and economic status, living with elderly individuals and the frequency of care for elderly people in their occupation on the AAS total score was not statistically significant. On the other hand, those who are 40 years of age and above, those who work more than 10 years, those who are willing to give care to elders and the physicians have a higher AAS mean total score. The ageism scores of the health professionals working in university hospital are positive but moderate. Larger studies should be carried out to evaluate the attitudes of health professionals towards elders and to improve their attitudes positively. [Med-Science 2019; 8(1.000): 117-22]